Pola Rescheduling Pada Pembiayaan Bermasalah Berakad Murabahah Di Bank Syariah - Andini Salamah; Arrison Hendry (Sekolah Tinggi Ekonomi Islam (STEI) SEBI, 2018)
This study aims to examine further related to problem financing, especially in murabahah financing. The research method used is a qualitative approach with descriptive analysis. The results of this study are, the rescheduling process undertaken by Islamic banks is to extend the term of financing and installment, with customer’s critera: decreased ability to pay, has a good business prospect, able to fulfill obligations after rescheduling. Second, Islamic bank must apply the provisions of the Fatwa DSN MUI that should not add to the remaining amount of bills, charging the cost in the rescheduling process is the real cost, and the extension of time payer must based on the agreement of both parties. Third, in the case of problem financing in effect after rescheduling is done, then the action that can be performed by the Islamic bank is to convert the murabahah financing contract into the qardh financing agreement.